The Effect of Democratic Leadership Style on Employee Performance at PDpark Makassar Raya - Isgunandar, Isgunandar; Mulyani, Ika; Niswaty, Risma (Pinisi Journal of Education and Management, 2022)
Leadership is an important element in a company, because without leadership a company will experience setbacks. A leader has different characteristics in leading his subordinates. This leader's behavior is called leadership style. This study aims to determine the effect of democratic leadership style on the performance of employees in PD. Greater Makassar Parking. This research is a quantitative research that shows causation. The sample in this study were 51 people using the Simple Random Sampling technique and 3 informants. Data collection techniques used are questionnaires, interviews, and documentation. The data analysis technique used is descriptive data analysis and inferential statistical analysis. Based on the results of the product moment correlation test, the relationship between variables is moderate. The results showed that the democratic leadership style was in the "Very Good" category while the employee's performance was in the "Very Good" category. Based on the results of simple linear regression analysis it was concluded that there is a positive and significant influence of democratic leadership style on employee performance. Choosing the right leadership style will have a good impact on the company. The results of this study state that the democratic leadership style tends to be open with employees, this can improve an employee's performance because they are able to work together and provide direct opinions with leaders. The results showed that the democratic leadership style was in the "Very Good" category while the employee's performance was in the "Very Good" category. Based on the results of simple linear regression analysis it was concluded that there is a positive and significant influence of democratic leadership style on employee performance. Choosing the right leadership style will have a good impact on the company. The results of this study state that the democratic leadership style tends to be open with employees, this can improve an employee's performance because they are able to work together and provide direct opinions with leaders. The results showed that the democratic leadership style was in the "Very Good" category while the employee's performance was in the "Very Good" category. Based on the results of simple linear regression analysis it was concluded that there is a positive and significant influence of democratic leadership style on employee performance. Choosing the right leadership style will have a good impact on the company. The results of this study state that the democratic leadership style tends to be open with employees, this can improve an employee's performance because they are able to work together and provide direct opinions with leaders. Based on the results of simple linear regression analysis it was concluded that there is a positive and significant influence of democratic leadership style on employee performance. Choosing the right leadership style will have a good impact on the company. The results of this study state that the democratic leadership style tends to be open with employees, this can improve an employee's performance because they are able to work together and provide direct opinions with leaders. Based on the results of simple linear regression analysis it was concluded that there is a positive and significant influence of democratic leadership style on employee performance. Choosing the right leadership style will have a good impact on the company. The results of this study state that the democratic leadership style tends to be open with employees, this can improve an employee's performance because they are able to work together and provide direct opinions with leaders.